Integer Programming Application to Optimize Profit of Samarinda Special Souvenir Production - Lisnawati; Syaripuddin; Qonita Qurrota A'yun (Jurnal Inotera, 2023)
Yulia's Amplang shop is one of the businesses engaged in the culinary field in the form of souvenirs typical of Samarinda City, namely Amplang. The amplang variants produced by this store include flat fish (original), shrimp, crab, squid and seaweed. Limitations and rising raw material prices make stores often experience difficulties in optimizing production profits. This study aims to determine the number of packages in one production process for each variant produced so as to obtain maximum profit. This study used the revised simplex method and then continued with the Branch and Bound Method, which is a method used to solve linear programming problems that produce solutions in integer form. From the analysis using this method, the optimal amount was obtained as many as 317 packages per production, including 144 flat fish flavors (original), 52 shrimp flavors, 34 crab flavors, 54 squid flavors and 33 seaweed flavors with the maximum profit obtained. namely Rp. 4,125,635. The application of this method resulted in an increase in profits of 5.53% or Rp. 216,103 in one production process compared to the previous company's profits.